Assessment of the Content and Process of Genetic Counseling: A Critical Review of Empirical Studies - Meiser, B.; Irle, J.; Lobb, Elizabeth; Barlow-Stewart, K. (Springer, 2008)
This article reviews studies that assessed the process and content of genetic counseling communication. A systematic search of the literature was undertaken of studies that audio- or videotaped genetic counseling sessions conducted by genetics health care providers and subjected them to communication analyses. A total of 18 studies (published in 34 articles) were identified that met the eligibility criteria. Studies show that providers speak more than clients, that a large proportion of communication is biomedical rather than psychosocial and that the teaching model of genetic counseling is widely implemented. Higher levels of counselor facilitation of understanding and empathic responses, lower levels of verbal dominance (ratio of counselor to client talk) and the provision of a summary letter of the consultation are associated with more positive client outcomes. Findings from these studies should be used as an evidence base for teaching and continuing education of genetic counseling providers.